How institutions shape the economic returns of public investment in European regions - Inmaculada Àlvarez Ayuso; Javier Barbero; Luis Orea; Andrés Rodríguez-Pose (European Commission, Joint Research Centre (JRC), 2023)
In this paper, we examine the impact of institutional quality on the returns on key drivers of economic growth in 230 European Union (EU) NUTS-2 regions from 2009 to 2017. To estimate region-specific elasticities, we employ a latent class modelling approach, considering the quality of government and the degree of authority in each region as mediators. Our findings reveal significant variation in the returns to education, physical capital investment, and innovation across regions. Moreover, we observe that changes in government quality and regional authority influence the ability of EU regions to leverage different types of investment effectively. These results emphasize the importance of considering the government quality in regions where investments are made in order to maximize the returns on European Cohesion investment.
Keywords: O43; E61; H54; R11; 330; Institutional quality; European funds; public investment; regional development